(untitled) (Research, Society and Development, 2022)
Personality disorders (PD) are not properly diseases, but anomalies of psychic development, being considered, in forensic psychiatry, as a mental health disorder. These disorders involve the disharmony of affectivity and excitability with deficient integration of impulses, attitudes and behaviors, manifesting itself in interpersonal relationships. Personality disorders, like other psychiatric diagnoses, are etiologically complex, being probably the result of the interaction of multiple genetic and environmental factors. The ICD, in its eleventh revision, describes eight types of specific personality disorders: paranoid, schizoid, schizotypal, antisocial, borderline, histrionic, avoidant, dependent, and obsessive-compulsive. Although the diagnosis of PD can be considered, it is important to avoid diagnosing patients who present themselves as difficult to manage, arouse anger or other intense emotions and demand a lot of attention, in critical situations, emergency care and from a single assessment, since there is evidence of a disparity in the diagnosis made in these circumstances compared to that established from an appropriate systematized interview.